PRAKTIK PENGUNGKAPAN SOSIAL: STUDI KOMPARATIF DI ASIA TENGGARA - Edy Supriyono; Djoko Suhardjanto (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2013)
AbstractThis research aims to examine the effect of corporate governance on the corporate social disclosure in the South East Asia companies as well as to test the difference of the level of corporate social disclosure (CSD) between three countries: Indonesia, Malaysia, and Thayland. Variables in the research are: the number of commissioners, board competence, the proportion of independent commissioners, audit committee size, the proportion of independent audit committees, and ownership of managerial. Global Reporting Initiative 2006 is used to measurement CSD. Sample in this study were drawn from the company's annual report on Indonesia Stock Exchange, Kuala Lumpur Stock Exchange, and Thayland Stock Exchange in 2009. There are a significant predictors namely the competency of the board of director, numbers of audit committee and proportion independent audit committees on corporate social disclosure. The number of commissioners, the proportion of independent commissioners, and ownership of managerial are not as determinant significant that only firms size and industry type. There are different corporate social disclosure practice in Indonesia, Malaysia and Thayland. Level of disclosure in Indonesia over an average of 40,14%, 58,52% in Malaysia, and 54,12% in Thayland. This is caused by differences in corporate governance practices in those countries.Keywords: corporate social disclosure, corporate governance, comparative study.AbstraksiPenelitian ini bertujuan untuk menguji pengaruh corporate governance terhadap pengungkapan sosial perusahaan pada perusahaan-perusahaan di Asia Tenggara serta untuk menguji perbedaan tingkat pengungkapan sosial perusahaan (CSD) antara tiga negara: Indonesia, Malaysia, dan Thailand. Variabel dalam penelitian ini adalah: jumlah komisaris, dewan kompetensi, proporsi komisaris independen, ukuran komite audit, proporsi komite audit independen, dan kepemilikan manajerial. Global Reporting Initiative 2006 digunakan untuk pengukuran CSD. Sampel dalam penelitian ini diambil dari laporan tahunan perusahaan di Bursa Efek Indonesia, Kuala Lumpur Stock Exchange dan Bursa Efek Thailand pada tahun 2009. Hasil penelitian menunjukkan adanya prediktor yang signifikan yaitu kompetensi dewan direktur, jumlah komite audit dan proporsi komite audit independen terhadap pengungkapan sosial perusahaan. Jumlah komisaris, proporsi komisaris independen, dan kepemilikan manajerial tidak sebagai penentu signifikan yang ukuran hanya perusahaan dan industri jenis. Ada perbedaan pengungkapan sosial perusahaan dalam praktik di Indonesia, Malaysia dan Thailand. Tingkat pengungkapan di Indonesia lebih dari rata-rata sebesar 40,14%; 58,52% di Malaysia dan 54,12% di Thailand. Hal ini disebabkan oleh perbedaan dalam praktik tata kelola perusahaan di negara-negara tersebut.Kata kunci: pengungkapan sosial perusahaan, tata kelola perusahaan, komparatif